8(x-4)-2(x-3)+9x=

Simple and best practice solution for 8(x-4)-2(x-3)+9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-4)-2(x-3)+9x= equation:


Simplifying
8(x + -4) + -2(x + -3) + 9x = 0

Reorder the terms:
8(-4 + x) + -2(x + -3) + 9x = 0
(-4 * 8 + x * 8) + -2(x + -3) + 9x = 0
(-32 + 8x) + -2(x + -3) + 9x = 0

Reorder the terms:
-32 + 8x + -2(-3 + x) + 9x = 0
-32 + 8x + (-3 * -2 + x * -2) + 9x = 0
-32 + 8x + (6 + -2x) + 9x = 0

Reorder the terms:
-32 + 6 + 8x + -2x + 9x = 0

Combine like terms: -32 + 6 = -26
-26 + 8x + -2x + 9x = 0

Combine like terms: 8x + -2x = 6x
-26 + 6x + 9x = 0

Combine like terms: 6x + 9x = 15x
-26 + 15x = 0

Solving
-26 + 15x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + 15x = 0 + 26

Combine like terms: -26 + 26 = 0
0 + 15x = 0 + 26
15x = 0 + 26

Combine like terms: 0 + 26 = 26
15x = 26

Divide each side by '15'.
x = 1.733333333

Simplifying
x = 1.733333333

See similar equations:

| 80=-39+c | | -6.8+-1.9= | | -113=-2x-3(-x+35) | | 3x-4=8x+16 | | 3m+v=-0.11+5v | | 2+1+f=-f+7f-2 | | 83=19+y | | -56x^2y^3/16x^4y^-1 | | 3x+14=98 | | 10(8)(x)=120 | | 48=-28+f | | -5(7-5)-8= | | s=3t^3-2t | | 1/4*1/9 | | -4(1-5b)=-124 | | -5(-5-7)+9= | | 0.5(x-1)=0.33(x+1) | | 20*-0.4= | | 2b/2+b/4-4/2=34/8 | | 2y^2=7y | | 2(9+5)-8= | | 62=-6x-2(-x-9) | | 4-20(-0.4)= | | 0=-16x^2+12-4x+3 | | 3*(1+n)=9+n | | -4y-2=9y-3 | | 7=3+6 | | 4-20(-8)= | | 0.20x+6=14 | | 10=25-5T-T^2 | | 6a-5=-3a | | 7/2x-3x=-1/2x+3/2+5/2x |

Equations solver categories